A bivalent protein r-PB, comprising PA and BclA immunodominant regions for comprehensive protection against Bacillus anthracis - Saugata Majumder; Shreya Das; Vikas Somani; Shivakiran S. Makam; Kingston J. Joseph; Rakesh Bhatnagar (Scientific Reports, 2018)
Abstract Anthrax infection is primarily initiated by B. anthracis endospores that on entry into the host germinate to vegetative cells and cause severe bacteremia and toxaemia employing an array of host colonisation factors and the lethal tripartite toxin. The protective efficacy of conventional protective antigen (PA) based anthrax vaccines is improved by co-administration with inactivated spores or its components. In the present study, using structural vaccinology rationale we synthesized a bivalent protein r-PB encompassing toxin (PAIV) and spore components (BclACTD) and characterized its protective efficacy against B. anthracis infection. Active immunization of mice with r-PB generated high titer circulating antibodies which facilitated the phagocytic uptake of spores, inhibited their germination to vegetative cells and completely neutralized anthrax toxins in vivo resulting in 100 % survival against anthrax toxin challenge. Proliferation of CD4+ T cell subsets with up-regulation of Th1 (IFN-γ, IL-2, and IL-12), Th2 (IL-5, IL-10) cytokines and balanced expression of IgG1:IgG2a antibody isotypes indicated the stimulation of both Th1 and Th2 subsets. The immunized mice exhibited 100 % survival upon challenge with B. anthracis spores or toxin indicating the ability of r-PB to provide comprehensive protection against anthrax. Our results thus demonstrate r-PB an efficient vaccine candidate against anthrax infection.